Early childhood education and care teachers’ experiences of using Early Childhood Quality External to assess process quality - Baustad, Anne Grethe; Tobiassen, May Liss Olsen; Smeby, Kristine Warhuus; Flormælen, Laila Skjei (Frontiers in Education, 2025)
IntroductionHigh-quality early childhood education and care (ECEC) positively influence children’s wellbeing and development. This study explores 18 teachers’ perspectives on the Early Childhood Quality (EQUAL) External tool—co-created by Norwegian ECEC teachers and researchers to assess process quality.MethodsSemi-structured interviews, conducted in pairs, were analyzed using thematic analysis.ResultsFindings suggest that, although the use of the tool was perceived by some teachers as overwhelming or demanding, its application may offer beneficial outcomes. External observations fostered awareness of teachers’ own and others’ practices, positioning it as a valuable tool for reflection, assessment and improvement of process quality. However, certain contents were perceived as challenging to observe and assess, highlighting the need for professional support and reflective dialog during implementation.DiscussionThe findings are discussed using theory and literature focusing on quality in ECEC, children’s development and learning, as well as on practice development. A possible implication for practice is the development of a quality improvement framework that seeks to integrate both practitioners’ and researchers’ perspectives. While the findings provide valuable insights, it is acknowledged that further research is necessary to validate and extend the findings across broader and more diverse contexts. Further research could also focus on how teachers apply professional judgment during observations and rating processes, or on how EQUAL External influences professional learning and practice.